Pengaruh Etos Kerja, Disiplin Kerja dan Pengembangan Karir Terhadap Prestasi Kerja Pegawai di Badan Perencanaan Pembangunan Daerah - Nur Annisa; Bobby Fahreza; Juli Gusnawita Sitepu; Wanny Septiani Wicaksini; Veronika Margaretta Silitonga; Supar Wasesa; Ismail Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Human resources in an organization are very important where human resources are needed in an organization for the progress of the organization. Employees are one of the components that determine the success of work activities within the organization. Serious attention must always be given to managing human resources, in this case employees. Work performance is the result of work that a person has achieved from their work behavior in carrying out work activities. In line with the development of the times and technology, one of the government agencies, namely the Regional Development Planning Agency (BAPPEDA), East Aceh Regency, has long started making changes in implementing administration, work mechanisms and services with the aim of ensuring that the agency is able to maintain work performance. However , a phenomenon that often occurs in BAPPEDA East Aceh Regency is the low work performance of employees which causes the administrative service process to be slow and many problems often arise. The decline in employee work performance is due to the lack of employee work discipline. Another problem is the work ethic which is still lacking. low level can be seen from a lack of optimizing one's potential, lack of cooperation between employees, lack of optimizing the time given, lack of friendliness, lack of discipline in work, etc. Work discipline is the real practice of employees regarding the rules contained in an organization. An employee's career is a series of activities or behavior related to an employee's experience and work activities from the time he joins an organization/company as a new employee until the employee retires/is laid off or dies. To improve the work performance of the Regional Development Planning Agency (Bappeda) of East Aceh Regency for each employee, this cannot be separated from the work ethic, work discipline and career development that these employees believe in. Employee discipline is one of the things that greatly influences the the level of work performance of an employee himself. Career development is the process of increasing a person's work abilities which encourages an increase in work performance in order to achieve the desired career. Career development activities are supported by the agency, so the agency expects feedback from employees, namely in the form of work performance. Work ethic has a positive and significant effect on the work performance of employees at the Regional Development Planning Agency (Bappeda East Aceh Regency). Work discipline has a negative and insignificant effect on the work performance of employees at the Regional Development Planning Agency (Bappeda East Aceh Regency). Career development has a positive and significant effect on employee work performance at the Regional Development Planning Agency (Bappeda, East Aceh Regency). Work ethic, work discipline and career development on employee work performance at the Regional Development Planning Agency (Bappeda East Aceh Regency)